Proces Verbaal. - Verkeerd Geparkeerd (VG) (Gent : Verkeerd Geparkeerd, 2001)
Fonds Suzan Daniel (FSD)
Periodiciteit : 2 maandelijks [?]
Redactie : postbus 535, 9000 Gent 1
Voortzetting van 'Verslag'
Nederlands
Periodiek
Keywords: Holebibladen